ARE YOU HAPPY EVEN WITHOUT YOUR MOBILE PHONE? (Identification of Nomophobia on Students of SMAN 1 Pangalengan Bandung) - Deni Sutisna; Dyah Indraswati (Jurnal Community, 2020)
Nomophobia is a phenomenon that occurs as a result of the development of communication technology, especially mobile phones, which some people unconsciously experience. This study aims to reveal the tendency of Nomophobia experienced by students of SMAN 1 Pangalengan, especially class 10 in the 2019-2020 academic year. Assessed by using a descriptive quantitative approach to reveal the phenomenon that is happening. This study uses an instrument developed by (Yildirim, 2014) called the NMP-Q instrument (Nomophobia Quessionaire). NMP-Q is a list of statements totaling 20 items covering four dimensions of Nomophobia: (1) unable to communicate, (2) loss of connection / connection, (3) unable to access information, and (4) giving up comfort. All items were assessed using a Likert scale ranging from 1 (strongly disagree) to 7 (strongly agree). The level or level of the nomophibia depends on the value obtained. ≤20 then no Nomophobia occurs, 21-60 means experiencing mild Nomophobia, 61-100 means moderate Nomophobia, and> 101 means severe Nomophobia. The results showed that 6% of students had mild Nomophobia, 46% of students had moderate Nomophobia, and 48% of students had severe Nomophobia, so it can be concluded that students of SMAN 1 Pangalengan in class 10 in the 2019-2020 academic year were identified as having Nomophobia.